Explant models for meniscus metabolism, injury, repair, and healing. (3rd July 2020) - Tarafder, Solaiman; Park, Gayoung; Lee, Chang H.
ABSTRACT: Purpose/Aim: Knee meniscus is a wedge-shaped fibrocartilaginous tissue, playing important roles in maintaining joint stability and function. Injuries to the meniscus, particularly with the avascular inner third zone, hardly heal and frequently progress into structural breakdown, followed by the initiation of osteoarthritis. As the importance of meniscus in joint function and diseases is being recognized, the field of meniscus research is growing. Not only development, biology, and metabolism but also injury, repair, and healing of meniscus are being actively investigated. As meniscus functions as an integrated unit of a knee joint, in vivo models with various species have been the predominant method for studying meniscus pathophysiology and for testing healing/regeneration strategies. However, in vivo models for meniscus studies suffer from low reproducibility and high cost. To complement the limitations of in vivo animal models, several types of meniscus explants have been applied as highly controlled, standardized in vitro models to investigate meniscus metabolism, pathophysiology, and repair or regeneration process. This review summarizes and compares the existing meniscus explant models. We also discuss the advantages and disadvantages of each explant model. Conclusion: Despite few outstanding challenges, meniscus explant models have potential to serve as an effective tool for investigations of meniscus metabolism, injury, repair and healing.